2012
DOI: 10.1186/1475-2840-11-130
|View full text |Cite
|
Sign up to set email alerts
|

Associations of sex hormone-binding globulin and testosterone with diabetes among men and women (the Saku Diabetes study): a case control study

Abstract: BackgroundSex hormone-binding globulin (SHBG) levels and sex hormones have been implicated in the pathogenesis of type 2 diabetes and cardiovascular diseases. As fatty liver has been suggested to be a major determinant of SHBG levels, we examined whether the associations of SHBG and testosterone with diabetes were independent of fatty liver.MethodsWe conducted a case–control study that included 300 diabetes cases (215 men and 85 women) and 300 matched controls from the Saku cohort study. Diabetes was defined b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
40
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 31 publications
10
40
0
4
Order By: Relevance
“…In our study, we found a significant increase in mean ± SD of BMI in patient groups (29.32.9 kg / m 2 ) in comparison with control subjects (27.91.7 kg / m 2 ) (p= 0.03).This result was matched with the results of Goto et al (14) and Huffman et al (35) , Oh et al , Ding et al (46) and Kalyani et al (17) who found that elderly diabetic postmenopausal females had higher WC and BMI than non diabetic females.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…In our study, we found a significant increase in mean ± SD of BMI in patient groups (29.32.9 kg / m 2 ) in comparison with control subjects (27.91.7 kg / m 2 ) (p= 0.03).This result was matched with the results of Goto et al (14) and Huffman et al (35) , Oh et al , Ding et al (46) and Kalyani et al (17) who found that elderly diabetic postmenopausal females had higher WC and BMI than non diabetic females.…”
Section: Discussionsupporting
confidence: 91%
“…This result was matched with result of Goto et al (14) who showed no association between testosterone and BMI in diabetic's elderly women. Also McTiernan et al (71) , Kalish et al (80) and Oh et al (43) they found no association between testosterone, BMI and WHR in diabetics postmenopausal women.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Evidence suggests that metabolic factors associated with DM impact on the hypothalamic-pituitary-testicular axis, 3 and there is a clear inverse relationship between testosterone levels and DM. [4][5][6] Since testosterone also plays an important role in the development and progression of prostate cancer, 7,8 lower levels of testosterone in diabetic patients may lessen the risk for prostate cancer. 1 The problem, however, is that DM is a progressive disease associated with a number of physiological changes that start before its clinical onset (figure 1).…”
mentioning
confidence: 99%